2020
DOI: 10.1155/2020/7305241
|View full text |Cite
|
Sign up to set email alerts
|

Association between Inflammatory Bowel Disease and Pancreatitis: A PRISMA-Compliant Systematic Review

Abstract: Background/Objectives. This systematic review was conducted to investigate the association between pancreatitis and IBD. Methods. MEDLINE, Embase, and CENTRAL were systematically searched for correlative studies till 2 November 2019. RevMan5.3 was used to estimate relevance. Results. Three studies with 166008 participants were included. The risk of pancreatitis significantly increased in the patients with CD (OR, 3.40; 95% CI, 2.70-4.28; P<0.00001) and UC (OR, 2.49; 95% CI, 1.91-3.26; P<0.00001). Increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
(62 reference statements)
1
10
0
Order By: Relevance
“…The reason for the lower severity of AP in patients remains unclear. Several studies have reported that the risk of AP increases in IBD patients 7,23,24 . The pathogenesis of AP in patients with IBD varies, including gallstones, autoimmune mechanisms, drug‐induced types including azathioprine and 5ASA, duodenal stenosis due to intestinal inflammation, and anatomical abnormalities 10,25–29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for the lower severity of AP in patients remains unclear. Several studies have reported that the risk of AP increases in IBD patients 7,23,24 . The pathogenesis of AP in patients with IBD varies, including gallstones, autoimmune mechanisms, drug‐induced types including azathioprine and 5ASA, duodenal stenosis due to intestinal inflammation, and anatomical abnormalities 10,25–29 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the risk of AP increases in IBD patients. 7 , 23 , 24 The pathogenesis of AP in patients with IBD varies, including gallstones, autoimmune mechanisms, drug‐induced types including azathioprine and 5ASA, duodenal stenosis due to intestinal inflammation, and anatomical abnormalities. 10 , 25 , 26 , 27 , 28 , 29 A multicenter cohort study reported that drug‐induced AP was the most common form of AP, followed by idiopathic AP.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of genetic susceptibility, immunological disturbances and environmental factors variably participate in the pathogenesis of pancreatic disease associated with IBD [ 1 ]. Nevertheless, while the contribution of genetics to the onset and progression of pancreatitis has been widely assessed, poor are the data about its role in pancreatitis associated with IBD [ 23 ].…”
Section: Role Of Genetics In Pediatric Pancreatitis and Its Association With Ibdmentioning
confidence: 99%
“…It is known that changes in microflora composition may result in a reduced microbial diversity, leading to immune disorders and susceptibility to disease, including pancreatitis and IBD [ 1 , 23 , 30 ]. IBD has been associated consistently with gut dysbiosis, low concentration of Firmicutes, such as Bifidobacterium, Clostridia and especially Faecalibacterium prausnitzii, and increased concentrations of Escherichia Coli [ 46 ].…”
Section: Role Of Genetics In Pediatric Pancreatitis and Its Association With Ibdmentioning
confidence: 99%
See 1 more Smart Citation